Application of Fuzzy Multiple Criteria Decision Making in the Employee Leave Application System using the Simple Additive Weighting (SAW) Method - adani, abdul harits; Sriani, Sriani (Sistemasi: Jurnal Sistem Informasi, 2024)
PT. Telkom Akses (PTTA) has constraints in the employee leave application management system, this is because the employee leave application process is still done manually and difficulties in determining the level of importance for employees who apply for leave. Therefore, a web-based application was built using FMCDM and the SAW Method. This study aims to improve efficiency and effectiveness in managing the employee leave application system by utilizing the Fuzzy Multi-Criteria Decision Making (FMCDM) approach using the Simple Additive Weighting (SAW) method at PT. Telkom Akses (PTTA). In order to make it easier for employees to carry out the deduction process and obtain complete and detailed information and rules related to deductions, the personnel department is expected to be able to create an online information system. To help with this, one of the fields of technology that can be utilized is soft computing technology. There are various methods that can be used to solve problems, one of which is the Fuzzy Multi Criteria Decision Making (FMCDM) method and the Simple Additive Weighting (SAW) method. The results of the study indicate that the web-based application that has been designed can help solve the problems faced by PT. Telkom Akses Medan STO Simpang Limun in terms of managing the employee leave application system and helping to determine the level of importance and ranking for employees who apply for leave accurately and efficiently, and the results of the application of FMCDM and the SAW Method in determining employee leave permits are that out of 7 employees who apply for leave, 2 employees get the highest rating results. The conclusion of this study is to help decision makers in determining employees who get leave permits based on relevant and transparent assessments of each employee who applies for leave.